Handbook of adhesion D.E. Packham. - Packham, D. E. (David Ernest), 1939- (John Wiley, 2005)
'Handbook of Adhesion' presents an extremely thorough review of adhesion technology and applications written in the form of short authoritative articles that are extensively cross-referenced and provide references for further reading.